1996
DOI: 10.1016/0014-5793(96)00802-2
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the lamin A gene during rat liver development

Abstract: We have studied the regulation of expression of the Atype lamins, which are constituents of the nuclear lamina. During rat liver development, high levels of lamin A and C mRNAs were observed in 15-day fetal fiver but were barely detectable in the adult. The chromatin conformation of the lamin A gene was sensitive to DNase I in 15-day fetal liver but became mostly insensitive in the adult. Lamin A and C proteins could be detected in fetal liver and persisted in the adult. Our evidence suggests that the lamin A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…4A, the relative concentration of lamin B in the nuclear matrices remained unchanged. In agreement with Hamid et al (18), and considerably earlier than reported previously (19), lamins A and C were already detectable in 16-day-old fetal livers (Fig. 4B, lane 1).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…4A, the relative concentration of lamin B in the nuclear matrices remained unchanged. In agreement with Hamid et al (18), and considerably earlier than reported previously (19), lamins A and C were already detectable in 16-day-old fetal livers (Fig. 4B, lane 1).…”
Section: Resultssupporting
confidence: 93%
“…The A-type lamins increase with terminal differentiation and growth arrest, suggesting a role for A-type lamins in cellular quiescence (20). In light of the recently reported decrease in transcriptional activity of the lamin A gene in adult rats (18), the increased concentration of lamin A could be the result of its slower turnover. Apparently, expression of lamin A/C, not lamin B, correlates with the differentiation stage of the hepatocyte.…”
Section: Resultsmentioning
confidence: 99%
“…We have observed that the -1877/+181 fragment of the rat lamin A promoter shows considerable activity in a mouse embryonal carcinoma cell line (PCC-4) (data not shown). We have earlier reported that this cell line does not express lamin A RNA (Hamid et al, 1996), which is consistent with several studies on lamin expression in embryonic cells. A possible interpretation of these findings is that the transiently transfected DNA does not acquire the repressed chromatin structure of the embryonic lamin A gene, and this structure is required for exclusion of ubiquitous transcription factors such as Spl and API.…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have established that lamin A and C proteins are expressed only in differentiated cells and are not detectable in early embryos or undifferentiated embryonal carcinoma cell lines (Stewart and Burke, 1987;Rober et al, 1989;Lehner et al, 1987;Benavente et al, 1985;Stick and Hausen, 1985). The expression of the mammalian lamin A gene has been shown to be primarily under transcriptional control during embryonic liver development in the rat (Hamid et al, 1996) and on differentiation of embryonal carcinoma cells induced by retinoic acid (Mattia era/., 1992), although an instance of posttranscriptional control has been reported (Lanoix et al, 1992). The expression of Drosophila A-type lamin during development is also under transcriptional control (Riemer et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation